An open-label phase I comparator-controlled clinical trial to assess tolerability and pharmacokinetics of IHL-675 A a fixed dose combination of cannabidiol plus hydroxychloroquine in healthy volunteers - George Williams Mbogo; Pia Kroner; Rosemarie Walsh; Jonathan Newchurch; Mark Robert Bleackley (Scientific Reports)
Abstract This was a phase I randomised comparator controlled clinical trial that assessed the pharmacokinetics (PK), and tolerability of IHL-675 A, a fixed dose combination (FDC) of cannabidiol (CBD) and hydroxychloroquine sulfate (HCQ), compared to the reference listed drugs Epidiolex (CBD) and Plaquenil (HCQ) in healthy volunteers (HVs). IHL-675 A is Incannex Healthcare Pty Ltd.’s proprietary product formulated using UniGel™ technology consisting of a solid, film coated HCQ tablet contained within a CBD-oil solution gel cap. Each IHL-675 A gel cap contains 75 mg of CBD and 100 mg HCQ. IHL-675 A is being developed for treatment of inflammatory conditions such as rheumatoid arthritis. This trial assessed the tolerability of IHL-675 A as well as pharmacokinetics of the active pharmaceutical ingredients CBD and HCQ as well as their major metabolites, compared to the reference listed drugs. The study included 3 treatment arms: IHL-675 A arm (150 mg CBD, 200 mg HCQ) and Plaquenil arm (200 mg HCQ) and Epidiolex (150 mg CBD) arm. Thirty-six participants were randomised into the 3 groups (12 per arm) and followed up for 4 weeks. Safety assessments including vital signs, electrocardiogram (ECG) parameters, and clinical laboratory parameters. Plasma concentrations of CBD, HCQ and their major metabolites, 7-OH-CBD, and 7-COOH-CBD, and desethylhydroxychloroquine (DHCQ), desethylchloroquine (DCQ), and bisdesethylhydroxy-chloroquine (BDCQ) were assessed at predefined timepoints across the monitoring period and PK parameters were determined and compared between treatments using noncompartmental methods and analysis of variance (ANOVA) of log-transformed values exposure PK parameters. All adverse events were coded using the current version of the Medical Dictionary for Regulatory Activities (MeDRA) by system organ class (SOC). IHL-675 A was generally well tolerated and had a similar adverse event profile compared to Epidiolex and Plaquenil. There were no SAEs reported in this study. Both CBD and HCQ were bioavailable when dosed in IHL-675 A. There were non-statistically significant differences between the pharmacokinetics of both CBD and HCQ when compared between IHL-675 A and Epidiolex or Plaquenil. There was approximately 50% increase in Cmax of CBD for IHL-675 A when compared with Epidiolex, and a slight increase of approximately 10% in AUC0−last and AUC0−inf. The 90% CI for the ratios of AUC0−inf, AUC0−last and Cmax of CBD all extended beyond the acceptance interval of 80% – 125%. The Cmax of HCQ for IHL-675 A was comparable to the reference product Plaquenil, with a geometric mean squares ratio of 96.5%. There was approximately 15% decrease in AUC0−last. The 90% CI for the ratios of AUC0−last and Cmax of HCQ extended beyond the acceptance interval of 80% – 125%. The ratio of AUC0−inf was not reliable for comparison between treatments, since the t1/2 was estimable for only 5 of 12 participants who received IHL-675 A. IHL-675 A was generally well tolerated when delivered as an oral fixed dose with no adverse events of concern or Serious Adverse Events (SAEs). Compared to the reference listed drugs for CBD (Epidiolex 150 mg) and HCQ (Plaquenil 200 mg), there was a slightly increased exposure to CBD and its metabolites for IHL-675 A, and slightly decreased exposure to HCQ. These results support the continued clinical development of IHL-675 A. Trial Registration: ACTRN12622000289718.